Cost and benefit of e - speed supervisor in express bus - Sidek, Shafie (UIKTEN, 2022)
Electronic Speed Supervisor, a device that discloses the real-time speed of express bus to passengers is proposed for express bus to solve both intentional speed violation and faulty engine speed limiter. Ex-ante cost-benefit analysis is carried out to assist managers in making decision between alternatives; (1) investment of RM3,000 per bus with monthly maintenance of RM100 per bus, (2) monthly rental and maintenance of RM300 per bus. Additional fare of 50cents per passenger is charged to gain revenue. alternative (1) is found to produce a better net present value, NPV and benefit cost ratio, BCR.